Criminal Liability for Perpetrators of Illegal Two-Wheeled Motorized Vehicle Racing in Gorontalo City - Abdullah, Mohamad Iqbal; Nur, Rafika; Insani, Nur (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Many violations of the law and crimes that occur in Indonesia, these violations or crimes can occur because of the lack of legal awareness in themselves. In criminology, crime means certain actions or deeds that are not approved by society. an action or negligence in acting, Seeing cases of traffic violations in the form of illegal racing, basically illegal racing is motorbike racing that is carried out illegally. The vehicles used are also not equipped with safety and security standards, this motorbike racing activity is usually carried out without using driving safety and security standards. This study uses an Empirical legal research method using a legal research method whose empirical facts are taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. Empirical research is also used to observe the results of human behavior in the form of physical remains and archives. The results of the study show; Review of Law No. 22 of 2019 concerning Traffic and Road Transportation The implementation of the law related to illegal racing in Gorontalo City is considered ineffective and not in line with the desired expectations. Although many drivers violate traffic rules and types of vehicles, the police continue to take action in accordance with Law Number 22 of 2019 by providing warnings. If the warning is ignored, violators will be subject to sanctions in accordance with legal provisions. The role of the police is vital in enforcing the law and maintaining public order. They have the responsibility to resolve conflicts or violations in accordance with the provisions of the Police Law as regulated in Law Number 2 of 2002, articles 13, 14, 15, and 16, by maintaining order, ensuring security, providing assistance to the community, and arresting lawbreakers in their area